Child and adolescent mental health services in Brazil: structure, use and challenges - Vagner dos Santos; Anna Fernández (Instituto Materno Infantil de Pernambuco, 2014)
Objectives: to examine the state of Child and Adolescent Mental Health (CAMH) services and to compare the availability and use of CAMH services across the five regions of Brazil. Methods: the Mental Health Matrix Model was used as a framework to describe the state of CAMH services. Documents and administrative datasets were consulted, covering the whole country and the five Brazilian regions as separate levels. This enabled crossregion comparisons and combination with thethree temporal dimensions (Input, Process andOutcome) Results: although there are national policies regulating CAMH, along with an integral protection doctrine, scarcity of services was unequally distributed across the regions. A number of trends relating to social development and mental health (e.g. intellectual disability treated prevalence) were also identified. Conclusion: substantial advances in CAMH policy characterize the contemporary Brazilian CAMH system, especially regarding the implementa tion of community based mental health services for children and adolescents. However, the data reveals great inequalities and geographic variation regarding social indicators, service structure and use.